2011
DOI: 10.1088/0004-6256/142/5/160
|View full text |Cite
|
Sign up to set email alerts
|

KEPLERECLIPSING BINARY STARS. II. 2165 ECLIPSING BINARIES IN THE SECOND DATA RELEASE

Abstract: The Kepler Mission provides nearly continuous monitoring of ∼156,000 objects with unprecedented photometric precision. Coincident with the first data release, we presented a catalog of 1879 eclipsing binary systems identified within the 115 deg 2 Kepler field of view (FOV). Here, we provide an updated catalog augmented with the second Kepler data release which increases the baseline nearly fourfold to 125 days. Three hundred and eighty-six new systems have been added, ephemerides and principal parameters have … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
238
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 403 publications
(253 citation statements)
references
References 22 publications
8
238
1
6
Order By: Relevance
“…As part of this exoplanet reconnaissance, 2165 eclipsing binaries are being observed of which 1322 are detached or semi-detached systems 13 We investigate these two subclasses of eclipsing binaries because the eclipse timing technique outlined in Supplementary Section 8 does not work well if the first and fourth contact points (start of ingress and end of egress) are not well defined. We also chose to omit systems with P < 0.9 days, as these in general also suffer from eclipse timing measurement difficulties owing to out-of-eclipse variations due to tidal distortions and reflection effects.…”
Section: The Search For Transiting Circumbinary Planet Candidatesmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of this exoplanet reconnaissance, 2165 eclipsing binaries are being observed of which 1322 are detached or semi-detached systems 13 We investigate these two subclasses of eclipsing binaries because the eclipse timing technique outlined in Supplementary Section 8 does not work well if the first and fourth contact points (start of ingress and end of egress) are not well defined. We also chose to omit systems with P < 0.9 days, as these in general also suffer from eclipse timing measurement difficulties owing to out-of-eclipse variations due to tidal distortions and reflection effects.…”
Section: The Search For Transiting Circumbinary Planet Candidatesmentioning
confidence: 99%
“…As part of its mission 11 to detect Earth-like planets via the transit method, Kepler is monitoring over 2,000 eclipsing binary stars 12,13 . From these we selected a sample of 750 systems with orbital periods ranging from 0.9 to 276 days, and for which eclipses of both stars occur.…”
mentioning
confidence: 99%
“…We do not know a priori which stars have such dilution. However, the effect on occurrence rates can be quantified via numerical simulation based on multiple star statistics from Kepler (84,85) and other (86) surveys.…”
Section: Requirements For Reliable Planet Occurrence Ratesmentioning
confidence: 99%
“…Although the transit light curve ( KIC3848972 as a false positive, which may consist of an evolved giant star that is redder and several magnitudes brighter than the eclipsing star. Slawson et al (2011) found an orbital period for this system that is twice as long. Moreover, we found a small difference between the odd and even transits in this system (0.000140) and a weak periodic background variability, which is very similar to an RS Canum Venaticorum-like distortion wave (see e.g.…”
Section: Exoplanet Candidate Kic3848972mentioning
confidence: 71%